1988
DOI: 10.1002/hep.1840080226
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol nucleation-influencing activity in t-tube bile

Abstract: Nucleation-influencing activity was determined in T-tube bile samples derived from patients with obstructive jaundice. Since native T-tube bile samples do not nucleate, nucleation-influencing activity was determined by measuring the influence of T-tube bile on the nucleation time of model bile. In the assay, T-tube bile was mixed with model bile, and the nucleation time of this mixture was compared with the nucleation time of a model bile supplemented with the same amount of lipid as present in the bile sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…It was reported that human bile contains several cholesterol crystallization-promoting glycoproteins and that biliary Hp and AGP have highly potent cholesterol crystallization-promoting activity at physiological concentrations (29,30). However, these promoters were identified from a ConA-bound fraction (31), and a correlation of its activity with fucosylation of glycoproteins has not been reported. Further studies will be required to determine whether fucosylated oligosaccharides on glycoproteins are associated with biological functions in bile as well as intracellular traffic in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that human bile contains several cholesterol crystallization-promoting glycoproteins and that biliary Hp and AGP have highly potent cholesterol crystallization-promoting activity at physiological concentrations (29,30). However, these promoters were identified from a ConA-bound fraction (31), and a correlation of its activity with fucosylation of glycoproteins has not been reported. Further studies will be required to determine whether fucosylated oligosaccharides on glycoproteins are associated with biological functions in bile as well as intracellular traffic in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…CABF was isolated from human T-tube bile by lectin affinity chromatography, as described by Groen et al 15 A 2-mL aliquot of CABF was incubated with 2 mg/mL pronase for 48 hours at 37°C.…”
Section: Concanavalin A-sepharose Binding Fractionmentioning
confidence: 99%
“…The major cholesterol crystallization promoting activity (CCPA) was localized to the Concanavalin A-binding fraction of biliary glycoproteins (CABF). [15][16][17][18] Groen et al 15 showed the CCPA of CABF to be pronase resistant and specific for biliary glycoproteins. This concept was supported by the observation of Pattinson and Willis 19 that the kinetics of cholesterol crystallization in bile was unaffected to digestion with pronase, even though pronase destroyed all biliary proteins visible on SDS-PAGE.…”
mentioning
confidence: 99%
“…4 Several factors may contribute to fast crystallization, such as biliary cholesterol supersaturation, increased concentration of bile in the gallbladder, 2,5 increased amounts of the hydrophobic bile salt deoxycholate, 6 a shortage of crystallizationinhibiting proteins, 7 or excessive crystallization promoting proteins. 8 The crystallization-promoting proteins have been partly isolated by means of lectin chromatography with concanavalin A-Sepharose. 8 This lectin binds glucose-and mannose-containing glycoproteins, which comprise about 10% of total biliary proteins.…”
mentioning
confidence: 99%
“…8 The crystallization-promoting proteins have been partly isolated by means of lectin chromatography with concanavalin A-Sepharose. 8 This lectin binds glucose-and mannose-containing glycoproteins, which comprise about 10% of total biliary proteins. Increased total protein concentration has been associated with faster cholesterol crystallization [9][10][11] and various concanavalin A-binding proteins such as immunoglobulins (Igs), 12,13 ␣1 acid glycoprotein, 14 haptoglobin, 15 and aminopeptidase-N 8,16 promote crystallization in in vitro systems.…”
mentioning
confidence: 99%